Interaction Between Market Orientation and Marketing Performance Through Dynamic Marketing Capabilities - Dicky Dwi Hartanto; Meutia Meutia; Liza Mumtazah Damarwulan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Indonesian handicrafts are one of the prides of Indonesia, because since 2015 handicrafts have been listed as one of the three sub-sectors that contribute to the GDP of the largest creative economy in Indonesia. Based on data from the Office of Cooperatives and Small and Medium Enterprises of Banten Province, there was a decline in the pottery business including, a decrease in income of 36% (thirty six percent) for the last 3 years (2019-2021). Therefore, pottery business actors need the ability to facing the market changes such as market orientation, to meet consumer needs that have a positive impact on marketing performance. The main problem in this study is how to improve the marketing performance of pottery business actors through market orientation and the purpose of this study is to analyze the role of market orientation variables with intervening variables, including dynamic marketing capabilities and market entry speed, in improving marketing performance. This research used quantitative methods with 83 pottery business actors in Banten Province as the object of research with sampling technique uses non probability sampling (purposive sampling) and using SEM PLS to analyze the data. Finding:  This research proves that Market Orientation affects Dynamic Marketing Capabilities and Market Entry Speed on marketing performance. In this study it was found: 1) Market Orientation has a negative effect on Marketing Performance 2) Dynamic Marketing Capability and Market Entry Speed have a positive effect on Marketing Performance 3) Dynamic Marketing Capability and Market Entry Speed mediate Market Orientation on Marketing PerformanceThis research proves that Market Orientation has a negative effect on Marketing Performance and prove that Dynamic Marketing Capabilities and Market Entry Speed mediate Market Orientation on Marketing Performance